2008
DOI: 10.1016/j.neuint.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Ca2+ and Cu2+ requirements of the FGF1–S100A13 interaction measured by quartz crystal microbalance: An initial step in amlexanox-reversible non-classical release of FGF1

Abstract: It is known that fibroblast growth factor-1 (FGF1) lacking a conventional signal peptide sequence shows non-classical release independent of the endoplasmic reticulum-Golgi system. Recent studies reveal that FGF1 is co-released with S100A13, a Ca 2+ -binding protein that acts as an extracellular cargo molecule. Although both FGF1 and S100A13 are Cu 2+ -binding proteins, the role of Cu 2+ , as well as that of Ca 2+ , in non-classical release, remains to be clarified. In the present study we examined the require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…[15][16][17] It has been reported that S100A13 is involved in the non-classical extracellular release of target molecules containing fibroblast growth factor-1 (FGF-1) and interleukin-1a. [9][10][11]19,34,35 In this study, we successfully showed that ProTa is another example of stress-induced non-vesicular extracellular release, using S100A13, a cargo molecule. Furthermore, we revealed that the C-terminal regions of ProTa and S100A13 are essential for their interaction, which precedes extracellular release of both proteins, and that caspase-3 cleaves off C-terminal regions of ProTa.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…[15][16][17] It has been reported that S100A13 is involved in the non-classical extracellular release of target molecules containing fibroblast growth factor-1 (FGF-1) and interleukin-1a. [9][10][11]19,34,35 In this study, we successfully showed that ProTa is another example of stress-induced non-vesicular extracellular release, using S100A13, a cargo molecule. Furthermore, we revealed that the C-terminal regions of ProTa and S100A13 are essential for their interaction, which precedes extracellular release of both proteins, and that caspase-3 cleaves off C-terminal regions of ProTa.…”
Section: Discussionmentioning
confidence: 82%
“…The addition of Strep-tagII-S100A13 to GST-ProTa immobilized on the sensor tip of a quartz crystal microbalance (QCM) decreased the quartz oscillation, as quantified by the oscillation unit (OU: DF in Hz), which represents the degree of interaction between the two proteins, as reported earlier. 19 The interaction between proteins was enhanced in the presence of Ca 2 þ , but not in the presence of Mg 2 þ or Cu 2 þ , and this enhancement was Ca 2 þ dependent in the range 0.1-200 mM (Table 1; Figure 4b). As the Ca 2 þ -dependent interaction was further enhanced by the addition of Cu 2 þ (Table 1), which has substantial binding affinity for S100A13, we used the addition of both Ca 2 þ and Cu 2 þ (100 mM and 100 nM, respectively) to determine the best ionic conditions for the interaction between GST-ProTa and Strep-tagII-S100A13.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Fibroblast growth factor‐1 (FGF1) was co‐released with S100A13, a Ca 2+ ‐binding protein that acts as an extracellular cargo molecule. QCM was used to determine affinities and kinetics in the presence of varying concentrations of Ca 2+ or Cu 2+ (Matsunaga and Ueda, 2008).…”
Section: Protein Interactionsmentioning
confidence: 99%